Etika Komunikasi Generasi Digital: Antara Kebebasan Berpendapat dan Tanggung Jawab Moral - Reihan Ak Ghani (Cendekia Madani Nusantara, 2025)
The development of digital technology has transformed the way humans communicate, particularly among the younger generation who live closely with social media and digital spaces. This article discusses the importance of communication ethics in maintaining responsibility and harmony in online interactions. Through a literature review and contextual reflection, this study highlights various challenges such as the spread of hoaxes, hate speech, and the decline of empathy in digital communication. The analysis shows that digital literacy and ethical awareness are the main keys for young people to communicate wisely, politely, and responsibly in an increasingly advanced technological era.